"Ye Shall Know Them by Their Fruits" A Mixed Methods Study on Corruption, Competitiveness, and Christianity in Europe and the Americas - García Portilla, Jason (Contributions to Economics,, 2022)
Why are historically Catholic countries and regions generally more corrupt and less competitive than historically Protestant ones? How has institutionalization of religion influenced the prosperity of countries in Europe and the Americas? This open access book addresses these critical questions by elucidating the hegemonic and emancipatory religious factors leading to these dissimilarities between countries. The book features up-to-date mixed methods from interdisciplinary research contributing to existing studies in the sociology of religion field by demonstrating-for the first time-the effect of the mutually reinforcing configuration of multiple prosperity triggers (religion-politics-environment). It demonstrates the differences in the institutionalization of Roman Catholicism and Protestantism by applying quantitative and qualitative methods and by performing a qualitative comparative analysis (QCA) of 65 countries. The author also provides a comprehensive survey and results of empirical research on different theories of development, focusing on the influence of religion.